M-10dm Oil Production Technology Based on Petroleum Distillates at Fergana Oil Refinery (For) (Eurasian Research Bulletin, 2022)
The ever-increasing demand for lubricating oils can only be met by expanding their range in accordance with the requirements of the equipment used and the technological capabilities of the oil refining industry. A technology for producing M-10 DM engine oil using the K-471 n additive package has been developed, which provides high performance characteristics